2015
DOI: 10.3945/ajcn.114.099168
|View full text |Cite
|
Sign up to set email alerts
|

Choline supplementation in children with fetal alcohol spectrum disorders: a randomized, double-blind, placebo-controlled trial

Abstract: This pilot study suggests that an additional evaluation of choline supplementation as an intervention for memory functioning in children with FASDs is warranted. The observed interaction between age and choline's effect on EI suggests that potential sensitive periods should be considered in future work. This trial was registered at clinicaltrials.gov as NCT01149538.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
100
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 50 publications
4
100
0
1
Order By: Relevance
“…Thus, although choline's critical period is quite large, and effects can be seen in later developmental periods, supplementation earlier in development has greater benefits (5, 7). Wozniak et al (14) observed improved memory in children aged 2.5 to #4 y but not in children aged .4 to 5 y, which was consistent with both the timing and pattern that have been shown in preclinical studies. When we examined age strata as a factor, the data did not indicate a differential treatment response within any particular age group of children.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…Thus, although choline's critical period is quite large, and effects can be seen in later developmental periods, supplementation earlier in development has greater benefits (5, 7). Wozniak et al (14) observed improved memory in children aged 2.5 to #4 y but not in children aged .4 to 5 y, which was consistent with both the timing and pattern that have been shown in preclinical studies. When we examined age strata as a factor, the data did not indicate a differential treatment response within any particular age group of children.…”
Section: Discussionsupporting
confidence: 59%
“…The null findings of this clinical trial were unanticipated because of the strong evidence that has suggested beneficial effects of choline supplementation in animal models of both typical development (39) and prenatal alcohol exposure (3)(4)(5)(6)(7)(8)10). However, this investigation was only one of a few trials to translate the aforementioned animal research to a human clinical trial of choline supplementation in FASDs, and previous studies, at earlier ages, have suggested some positive beneficial effects (13,14). Because of the early stage of this field of research, factors may have contributed to the divergent findings that were observed in this study compared with in other clinical studies and with the preclinical data.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations